Mixed Reality Virtual Device (MRVD) for seamless MR-IoT-Digital Twin convergence - Lee, Seungwoon; Kim, Sijung; Roh, Byeong hee (Internet of Things (Netherlands), 2024)
Mixed Reality (MR) extends Augmented Reality (AR) by emphasizing real-time interactions and providing a more immersive experience with the seamless integration of contextual elements, such as spaces, situations, objects, and user behaviors. MR creates new opportunities across fields, such as the Internet of Things (IoT) and Digital Twins (DT), and advancements in Artificial Intelligence (AI). However, integrating these technologies poses challenges for data synchronization, particularly for MR devices with limited computing resources. This study proposes a novel architectural concept, called the MR virtual Device (MRVD), to address the problem. MRVD serves as a virtual counterpart to the MR physical device (MRPD), optimizing computation and communication using container technologies to enhance availability, portability, and scalability. By handling resource-intensive tasks, MRVD boosts performance and consistency, thereby improving the effectiveness and efficiency of the MR-IoT-DT convergence. Our experiments demonstrate MRVD's concrete benefits in overcoming these challenges, offering a promising approach for future convergence applications.
Keywords: Augmented Reality (AR); Digital Twins; Internet of Things (IoT); Mixed Reality (MR); MR-IoT convergence